THE CONCEPT OF PHONOLOGICAL INTERFERENCE IN LANGUAGE ACQUISITION («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
In recent decades, the world around us has become increasingly multicultural.People are in regular contact not only with other cultures, but also with languages. Naturally, every language owes particular linguistic peculiarities and these peculiarities are clearly manifested whenever a language is being learnt or thought. The article discusses the issue of phonological interference as well as its influences on language mastering process.
Keywords: English language teaching, phonological interference, English sounds, natural tendency, pronunciation, phonetic, language experience, phonology, vowel length, types of interference, classification of interference.